(untitled) (Journal of Hama University, 2024)
Aim: To compare the effect of multiple usage and coarseness of diamond burs on marginal microleakage of resin composite restorations. Materials and methods: Ninety extracted primary molars were chosen. The sample was randomly divided into three groups: N1=N2=N3=30. Group (1) was prepared by using super coarse diamond burs. Group (2) was prepared by using coarse diamond burs. Group (3) was prepared by using medium coarse diamond burs. All cavities were restored by resin composite, then the teeth were thermocycled and immersed in 5% solution of methylene blue dye for 12 hours. Then the teeth were sectioned vertically, dye penetration was evaluated using a stereomicroscope at the occlusal and gingival margins. Data were collected and statistical analysis was conducted. Results: The results showed that the multiple use of super coarse diamond burs caused no statistically significant difference on occlusal and gingival microleakage (P>0.05). However, the multiple use of coarse and medium diamond burs caused statistically significant difference on gingival marginal microleakage (P<0.05). Conclusion: Under the conditions of this study, it can be concluded that the multiple use of super coarse diamond burs did not affect on occlusal and gingival microleakage. Whereas the multiple use of coarse and medium diamond burs affected only on gingival marginal microleakage.